(untitled) (Experimental biology, 2009)
The latent signals of splice site according to rules of processing of pre-mRNA in nucleus of plant cells was revealed. Optimal vector for cloning cDNA of HAFP and computer modeling of recombinant constructions design containing his-tag on the C - end of protein has been carried out. Amplification cDNA of HAFP by RT – PCR has been carried out.